Drastically enhanced tetracycline degradation performance of a porous 2D g-C3N4 nanosheet photocatalyst in real water matrix: Influencing factors and mechanism insight. (December 2022) - Ghosh, Utpal; Pal, Anjali
Abstract: Porous 2D nanosheets are an emerging class of materials with exciting physical, chemical, optical, and electronic characteristics. This study reported the facile synthesis of a porous 2D g-C3 N4 nanosheet photocatalyst through a simple chemical exfoliation route. The morphological characterization of the samples confirmed its porous 2D nanosheet structure with an approximate thickness of 2.5 nm. The as-prepared photocatalyst displayed a 4.2-fold enhanced tetracycline (TC) degradation rate coefficient compared to the pristine g-C3 N4 under LED illumination. Further, the porous 2D g-C3 N4 nanosheet photocatalyst exhibited superior TC degradation efficacy in a real water matrix. The synergistic effect of higher pH, presence of carbonate and bicarbonate anions, and the existence of humic substances could have elevated the degradation performance in the real water matrix. Moreover, the as-synthesized catalyst demonstrated remarkable stability and recyclability even after the four-cycle recycling experiment. A possible photocatalytic mechanism has been proposed following the findings of the radical trapping experiment. It is believed that this study would inspire further fabrication of other porous 2D nanosheet photocatalysts. Graphical abstract: Unlabelled Image Highlights: Fabrication of a porous 2D g-C3N4 photocatalyst is reported. The as-synthesized catalyst demonstrated an excellent degradation efficiency towards TC. The TC degradation efficiency further improved in presence of real water matrix. Higher pH, carbonate and bicarbonate anions, and humic substances in real water influenced the degradation process. h + and O2 − was the predominant reactive species, whereas OH played a minor role.